Letter - Reynolds, Bert
013-0075-001 Chester Trades Council & Divisional Labour Party. Headquarters — People's Hall, Delamere Street, Chester. President : Mr. T. BILLINGTON. Financial Secretary : Mr. H. C TEASDILL, "Valhalla," Vicar's Cross, Chester. General Secretary: COUN. BERT REYNOLDS, J.P. "FAIRHOLME," 6. MEADOWS LANE, CHESTER. June 11th 1940. Dear Sir Walter. You may have heard of the plight of a Mr Frank Ryan who is now serving a sentence of 30 years imprisonment in Spain. He was sentenced to death along with a Mr Tom Jones of Rhos, Wrexham. The latter was released and is now home and on April 18th last along letter appeared in the 'Manchester Guardina' setting full details above the signature of Tom Jones. This Council had the matter under consideration at its April Meeting and I was instructed to write the Spanish Ambassador in London a letter of protest. This was done on May 4th,and read as follows,- "I am directed by this Council to draw your attention to the "position of Mr Frank Ryna. This man served in the International "brigade in Spain during the Civil War. He was sentenced to "death by the Franco Government, which was later commuted to 30 "years imprisonment. He is now serving that sentence under most "abominable conditions. He is by no means a strong man "physically, and there is every liklihood of his early death "unless something is done immediately to secure his release. This Council views the sentence as a most brutal and "inhuman one,and calls upon your Excellency to use your good "office to secure his early release, and trust you will convey "the purport of this letter to your Government." We have not received even an acknowledgement from the Spanish Ambassador, and I have been instructed to ask if anything has been done, or can be done, by you. Personally I realise I should have communicated with you in the first place before writing the Ambassador, but it just didn't occur to me at the time. I must also say things have changed very considerably in the War situation since this matter was first considered, and of course now appears to be a very trivial affair at such a time. I must also take this opportunity of expressing our very sincere pleasure on your appointment to the Privy Council. Warmest regards. Yours sincerely Bert Reynolds Hon. gen. Secty. 292/946/13/75